Effect of roasted rice bran on the quality characteristics of biscuits developed with cassava starch - LANGA, Hermenegildo Vaz Moisés; EDUARDO, Maria; MOTANI, Karina Sultane; FRANCISCO, José da Cruz; LABANCA, Renata Adriana (Food Science and Technology, 2025)
This study aimed to evaluate the effect of roasted rice bran on the quality of cassava starch biscuits. The rice bran was submitted to heat treatment at 102.5 ± 2.5°C, with a roasting time that varied between 3 and 7 min. The optimal time for roasting was 5 min, with the bran having the characteristics of moisture (wet basis): 1.52% ± 0.20%, acidity: 0.24% ± 0.01% and lipids: 20.39% ± 0.18%. Four biscuit formulations were produced with 5, 10, 15, and 20% of roasted rice bran and a standard formulation (100% wheat flour). The nutritional value and sensory analysis of the biscuits were analyzed. The shelf life was tested for 60 days, at 30 ± 2°C, spaced 20 days apart for each measurement. The biscuit with rice bran roasted up to 15% proved to be acceptable from a nutritional value (ash: 2.54% ± 0.09%, proteins: 9.28% ± 0.19%, lipids: 20.78% ± 0.15%, fibers: 2.94% ± 0.03% and caloric value: 468.183 ± 0.57 kcal), water activity: 0.357% ± 0.028% and obtained an acceptance rate above 80%. The new biscuits produced were within acceptable quality standards for human consumption and it was concluded that roasted rice bran can be used as an ingredient in the production of biscuits with high nutritional and sensory quality.